THE INFLUENCE OF HUMAN RESOURCES MANAGEMENT TECHNOLOGY DEVELOPMENT: (Application of Electronic Human Resource Management in the Human Resource Development System of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in the Era of the Industrial Revolution 4.0) - Rahman, Noor; Hartanto, Heru Dwi; Khuzaini, Khuzaini; Shaddiq, Syahrial (Program Studi Manajemen, 2023)
Technological advances that continue to develop have had an impact on current management practices and are inseparable from human resource management practices. These practices in the Industrial 4.0 era. now it is inseparable from E-HRM. In running an E-HRM information system, of course, an organization must have adequate technology assets. In this case the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency follows developments in the current era in its application in terms of Human Resource Development. The Ministry of ATR/BPN pays adequate attention to the development of apparatus work competencies both in terms of quality and quantity both Knowledge, Expertise, Skills and Attitudes so that they can carry out their duties and positions in a professional manner.